Find the position of the particle.  a(t) = t2 − 9t + 6,    s(0) = 0,    s(1) = 20   s(t)= A particle is moving with the given data. Find the position of the particle.   a(t) = t2 −...

Find the position of the particle.

 a(t) = t2 − 9t + 6,    s(0) = 0,    s(1) = 20   s(t)=

A particle is moving with the given data. Find the position of the particle.

 

a(t) = t2 − 9t + 6,    s(0) = 0,    s(1) = 20   s(t)=_______________

Expert Answers info

sciencesolve eNotes educator | Certified Educator

calendarEducator since 2011

write5,349 answers

starTop subjects are Math, Science, and Business

You need to remember that position of particle may be found if the speed is given such that:

`s = v*t`

The problem provides you the function of acceleration, hence you should remember that `a(t) = (dv)/(dt),`  hence `a(t)dt = dv` . You need to integrate the equation `a(t)dt = dv`  such that:

`int a(t) dt = int dv =gt int (t^2-9t+6)dt=v(t)`

`v(t) = int t^2 dt - int 9t dt + int 6dt`

`v(t) = t^3/3 - 9t^2/2 + 6t + c_1`

You need to use the relation  `v(t) = (ds)/(dt)`  such that:

`ds = v(t)dt =gt int ds = int v(t)` dt

`s(t) = int(t^3/3 - 9t^2/2 + 6t + c_1) dt`

`s(t) = t^4/12 - 9t^3/6 + 6t^2/2 + c_1*t + c_2`

`s(t) = t^4/12 - 3t^3/2 + 3t^2 + c_1*t + c_2`

The problem provides the informations s(0)=0 and s(1)=20, hence, substituting 0 and 1 for t in s(t) yields:

`c_2=0`

`1/12 - 3/2 + 3 + c_1 = 20`

`c_1 = 17 + 3/2 - 1/12`

`c_1 = (204 + 18 - 1)/12`

`c_1 = 221/12`

Hence, evaluating the function s(t) under given conditions yields `s(t) = t^4/12 - 3t^3/2 + 3t^2 + 221t/12.`

check Approved by eNotes Editorial



najm1947 | Student

acceleration is rate of change of velocity = a(t) = d2x/dt2

I shall be using 'S' for integral sign in this question.

velocity = v(t) = S(d2x/dt2).dt = S(t2-9t+6)dt

= t3/3-9t2/2+6t+j where j is the constant of integration

distance = s(t) =S(v(t)).dt = S(t3/3-9t2/2+6t+j)dt

= t4/12-9t3/6+6t2/2+j.t+k where k is the constant of integration

we know that for t=0, s(0)=0

substituting these values in s(t) we get k = 0

also for t=1, s(1) = 20

substituting the values of k and s(1) in s(t) we get:

4/12-9/6+6/2+j = 20

or j= 20-1/3+3/2-3 = 109/3

subtituting the values of j, k in s(t) we get:

s(t) = t4/12-9t3/6+6t2/2+109t/3 or

s(t) = t4/12-3t3/2+3t2+109t/3

check Approved by eNotes Editorial